(untitled) (Journal of The Colloquium for Information Systems Security Education, 2016)
When looking at the next generation of trusted computing initiatives, secure packet content has to be one of the main concerns. The optional nature associated with securing the information in the packets, in conjunction with the risks associated with malware and hackers has to force the industry to move to an “encryption at birth” approach (packet structure should implement encryption) that should be an integral part of the out of the box design as opposed to a commodity. In this paper, we will introduce the recent research in the use of Trusted Platform Modules (TPMs) 2.0 as the main vehicle to encrypt packets communing out of network interface controllers (NICs) and have the routers incorporate the TPMs to provide packet deciphering, remote attestation, TPM Quarantine and serve as the central processing unit of a secure packet delivery Infrastructure.